Living tradition of Maria Martinez - Peterson, Susan (Kodansha International Tokyo, 1977)
Given in memory of Ethel A. Tsutsui, Ph. D. and Minoru Tsutsui, Ph. D
46969
Keywords: Martinez, Maria -- ca.1885-; Southwest; Tewa pottery; Tewa women potters; Tewa women potters -- Biography -- New Mexico San Ildefonso Pueblo; San Ildefonso Pueblo, New Mexico -- Biography